Bone mineral density and the level of active metabolites of vitamin d in postmenopausal women with spinal osteochondrosis - Kosterin, Sergey; Maltseva, Valentyna; Ashukina, Nataliya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
In the elderly and senile age, osteoporosis and spinal osteochondrosis are found with high frequency, which determines the study of their common development mechanisms. Objective: to study the level of 25(OH)D and 1.25(OH)2D3 and indicators of bone metabolism in the blood serum of postmenopausal women with spinal osteochondrosis and low bone mineral density (BMD). Methods: a retrospective analysis was performed using bone densitometer (Explorer QDR W, Hologic) data; BMD of the lumbar spine and proximal femur was assessed in 123 postmenopausal women with clinically and radiologically confirmed spinal osteochondrosis. The active serum metabolites of vitamin D (1.25(OH)2D3, 25(OH)D) were studied in the blood serum of patients by enzyme-linked immunosorbent assay; total and ionized calcium, phosphorus, magnesium, acid and alkaline phosphatase activity were determined. Results: in postmenopausal women with spinal osteochondrosis and decreased BMD, the average values of 25(OH)D were recorded at the level of insufficiency, and 1.25(OH)2D3 was at deficiency level. Among them osteoporosis was diagnosed in 67.5 %. A reduced level of magnesium was detected in 52.8 % (65) of the women examined, a reduced level of ionized calcium was detected in 60.9 % (75). Moreover, in patients with a deficiency of 25(OH)D, the serum magnesium level was on average lower than normal and by 1.2 times (p < 0.05) lower compared to the group with 25(OH) D deficiency. The level of total calcium was lower than the reference values in 26.8 % (33) patients, phosphorus was lower in 4.1 % (5). Conclusions: low BMD is associated with deficiency and insufficiency of 25(OH)D and 1.25(OH)2D3 in 100 % of postmenopausal women with spinal osteochondrosis. A decrease of the level of 25(OH)D is accompanied by a low level of serum magnesium, which should be considered when prescribing compensatory therapy of vitamin D.